Drought priming mechanisms in wheat elucidated by in-situ determination of dynamic stomatal behavior - Yang, Mengxiang; He, Jiawei; Sun, Zhuangzhuang; Li, Qing; Cai, Jian; Zhou, Qin; Wollenweber, Bernd; Jiang, Dong; Wang, Xiao (Frontiers in Plant Science, 2023)
Stomata play a critical role in balancing photosynthesis and transpiration, which are essential processes for plant growth, especially in response to abiotic stress. Drought priming has been shown to improve drought tolerance. Lots of studies have been done with the response of stomatal behavior to drought stress. However, how the stomatal dynamic movement in intact wheat plants response to drought priming process is not known. Here, a portable microscope was used to take microphotographs in order to in-stiu determination of stomatal behavior. Non-invasive micro-test technology was used for measurements of guard cell K+, H+ and Ca2+ fluxes. Surprisingly, the results found that primed plants close stomatal much faster under drought stress, and reopening the stomatal much quicker under recovery, in relation to non-primed plants. Compared with non-primed plants, primed plants showed higher accumulation of ABA and Ca2+ influx rate in guard cells under drought stress. Furthermore, genes encoding anion channels were higher expressed and K+ outward channels activated, leading to enhanced K+ efflux, resulting in faster stomatal closure in primed plants than non-primed plants. During recovery, both guard cell ABA and Ca2+ influx of primed plants were found to be significantly reducing K+ efflux and accelerating stomatal reopening. Collectively, a portable non-invasive stomatal observation of wheat found that priming promoted faster stomatal closure under drought stress and faster reopening during post-drought recovery in relation to non-primed plants, thereby enhancing overall drought tolerance.